Inclusive smart cities: theory and tools to improve the experience of people with disabilities in urban spaces. - Oliveira Neto, João Soares de (2018)
Cities have employed technologies in several domains to improve the delivery of public services, attend citizens\' demands, and measure the consumption of natural resources. Known as Smart Cities, these initiatives aim to increase the overall citizens\' quality of life, and they have already had a positive impact on the way citizens interact with urban spaces, services, and with each other. On the other hand, urban spaces can be considered as a threat to the independence and autonomy of people with disabilities. In fact, according to the Social Approach, disability is not in the individual, but in society and the environment, which does not provide adequate conditions for the individual to fully participate and be a citizen of social, professional, educational, recreational activities, and so on. Society and the environment need to be corrected and their deficiencies compensated to include a significant portion of the population that is excluded from a range of activities when their abilities are not addressed in urban communication processes. Although this group of citizens has gained access to education, work and leisure, it is necessary to confront the city and all its challenges in order to enjoy these rights. In order to extend the benefits of Smart Cities to people with disabilities, we first proposed the idea of an Inclusive Smart City, which employs Smart Cities technology to provide a better urban experience for people with disabilities while overcoming accessibility barriers in urban spaces. To achieve this goal, we began using a multi-instrument approach to collect data from different stakeholders - people with disabilities, professionals that work with people with disabilities, accessibility-related experts, and policymakers -, aiming at understanding the obstacles that people with disabilities face when they are moving around the city, the strategies they use to solve unexpected problems, and how they interact with other people and with urban facilities. Based on an empirical observation, literature review and results collected using this multiinstrument approach, we first defined Inclusive Smart Cities. Then, we proposed some tools to support practitioners and researchers involved in the development of digital urban assistive technologies with the Inclusive Smart City\'s vision in mind: a list of requirements, a political structure, an implementation/operation methodology, a business model, a conceptual model, and a system architecture. According to the conceptual model we introduced, people with disabilities are able to interact with inclusive smart objects that are available in urban spaces to obtain information about the environment around them, enabling them to navigate and explore cities in an innovative way. In Inclusive Smart Cities, inclusive smart objects provide people with disabilities with user-adapted information and services, focusing on the individuals\' abilities rather than their disabilities. Moreover, the system architecture is based on equipping users and the environment with smart technologies, aiming at supporting a symbiotic relationship between citizens and inclusive smart objects, a web-based user interface to enable public agents and local authorities to register and maintain the information required by the Inclusive Smart City platform, and the Cloud infrastructure, responsible for storing system data and processing user requests. Finally, we further demonstrated a Proof of Concept to assess the experience that people with disabilities would have when using an Inclusive Smart City solution. To accomplish that, we mapped a block of Paulista Avenue, in São Paulo, Brazil, as a sequence of QR codes. In a simulated circuit, when users read each code, they received location-based information and services related to the object linked to the code. The participants evaluated the UrbanAssist application positively and recognized the relevance of the functionalities and resources provided by the application, which gave them an inventive interface to explore the urban environment in a new, safer and effective way. In conclusion, this new technology has the potential not only to improve the independence and autonomy of people with disabilities in urban spaces, but also to enable them to play a proactive role in society as a whole.